Model Pembelajaran ERCORe dipadu Blended Learning untuk Kemandirian Belajar Biologi Siswa - Nur Ismirawati; Sulvianti; Asrinan (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2022)
Blended Learning has both advantages and limitations. Especially in the Biology subject which contains Biology material, it is not only related to the concept of concrete scientific facts, but also the concept of abstract objects. This study aims to determine the response of students and teachers to self-regulated learning through Blended Learning. This research is a survey. The sample in this study were teachers and students of class X SMA Parepare. Data analysis Data analysis of research results was carried out with qualitative descriptive analysis in the form of descriptions based on research findings. The results showed that there were main problems experienced by class X students in learning biology, students had difficulty understanding the material, the emergence of misconceptions, students became less focused in learning. Meanwhile, the teacher's perception is that it is difficult to control student learning, and it is difficult to understand students. Based on these results, it can be concluded that there are many obstacles experienced by students and teachers in learning biology, so that it requires attention and good teaching techniques to improve learning outcomes and the quality of student learning.